Detection of Cytochrome B Pork in Packaged Meatball from Traditional Markets around Jakarta - Kurniah, Allen Nurul; Puspitasari, Riris; Perdana, Analekta Tiara (Universitas Muhammadiyah Surakarta, 2020)
Meatballs are one of the favorite foods for Indonesian people. Meatball products are generally known to be based on beef. But there are cases that changed the basic ingredients of meatballs, beef into pork. This research was conducted to detect the presence of pork in packaged meatball products sold at Traditional Markets. Identification is carried out with the principles of molecular biology in the form of the PCR process. Meatball samples were previously subjected to DNA extraction. PCR was performed to determine pork genes using cytochrome b primers with an amplicon length of 130 bp. The cytochrome b gene can be found in every animal cell, but it has a specific characteristic that is only present in certain animal cells. Based on PCR results it is known that most of the samples did not contain pork marked by the absence of a DNA band that appeared and parallel to the 130 bp band on the ladder. However, there are two samples that appear DNA bands and are thought to contain pork. These results are followed by a sequencing process to clarify the results of the PCR process.